Molecular diagnosis of drug resistance tuberculosis In the Districts of Tamilnadu - SURESHBABU.R,; LAKSHMI MURALI. A,; PALANISWAMY.M, (International Journal of Pharma and Bio Sciences, 2016)
To diagnose the multi-drug resistant Mycobacterium tuberculosis by using molecular methods from pulmonary specimens of presumptive TB suspects belonging to the districts of Tamil Nadu. Two thousand three hundred and thirty five (2335) clinical specimens of presumptive MTB patients were collected from 23 districts of Tamil Nadu between the period of January and March 2015. Smear microscopy was performed by LED fluorescent microscopy. All smear positive samples were tested using Line Probe Assay (LPA) and smear negative samples were tested by Xpert MTB/RIF (Xpert) to detect the percentage of drug resistance pattern and to identify MTB complex. Among 1235 smear positives subjected to LPA method; 116 (9.4%) MTB was not detected and 3 (0.2%) showed invalid result; 1116 (90.4 %) strains showed MTB positive; 896 (80.3 %) were sensitive for both rifampicin (RIF) and isoniazid (INH) drugs; 128 (11.5 %) were resistance for INH; 18 (1.6 %) resistant for RIF and58 (5.2 %) were resistance for RIF and INH and smear negative specimens were subjected to Xpert, Out of 1090 specimens; 647 (59.4 %) MTB was not detected; 30 (2.8 %) showed an invalid/error results; 413 (37.9 %) strains showed MTB positive of which 379 (91.8 %) were sensitive for RIF, 24 (5.8 %) showed resistant for RIF and 09 (2.2 %) showed MTB detection and RIF Indeterminate. LPA and Xpert molecular technology are the rapid, feasible and reliable methods for the detection of multi drug resistant (MDR) mutation.